Correlation of recurrence rates and times with posttreatment human papillomavirus status in patients treated with loop electrosurgical excision procedure conization for cervical squamous intraepithelial lesions. Issue 1 (1st January 2008) - Prato, B.; Ghelardi, A.; Gadducci, A.; Marchetti, I.; Di Cristofano, C.; Di Coscio, G.; Bevilacqua, G.; Genazzani, A. R.
Abstract : The aim of the present study was to assess recurrence rates and times in patients with squamous intraepithelial lesion (SIL) of the uterine cervix treated with loop electrosurgical excision procedure (LEEP) conization, in order to define categories of patients who have a different risk of recurrence and who need a different surveillance protocol. This study was carried out on 119 consecutive patients who underwent LEEP. All patients were followed up with cervical smear and colposcopy after 3, 6, and 12 months in the first-year posttreatment, and every 6–12 months afterwards. Human papillomavirus (HPV) testing was performed at the time of LEEP and repeated 3–6 months later. The histologic examination of LEEP specimens revealed stage IA1 squamous cell cervical cancer in 4 (3.4%) cases, high-grade SIL in 75 (63%) cases, and low-grade SIL in 40 (33.6%) cases. The four patients with stage IA1 cervical cancer were not included in the further analyses. Disease recurred in none of the 50 patients with negative posttreatment HPV testing, in 4 (9.3%) of the 43 patients with positive posttreatment HPV testing and negative surgical margins, and in 8 (36.4%) of 22 patients with positive posttreatment HPV testing and positive margins. The combined evaluation of surgical margin status and posttreatment HPV testing could allow to subdivide patients treated with LEEP into categories at different risk of recurrence, requiring new tailored surveillance procedures.